FINANCIAL LITERACY, SOCIAL CAPITAL, AND SUSTAINABLE PERFORMANCE: MEDIATING ROLES OF STRATEGIC AGILITY AND SOCIAL INNOVATION - Shelly Shintyasari; Yesi Mutia Basri; Novita Indrawati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
Sustainable performance is increasingly important for cooperatives as they are expected to create economic, social, and environmental value simultaneously. This study examines the effects of financial literacy and social capital on sustainable performance, with strategic agility and social innovation as mediating variables. Grounded in the Resource-Based View and Dynamic Capabilities Theory, data were collected from 268 active cooperatives in Kuantan Singingi Regency, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy and social capital positively influence sustainable performance, with social capital emerging as the strongest predictor. Strategic agility and social innovation significantly mediate the relationship between financial literacy and sustainable performance. However, neither mediator significantly explains the effect of social capital on sustainable performance. This study contributes by validating a dual mediation framework that explains how organizational resources generate sustainable performance through different mechanisms. Financial literacy operates through capability-building processes, whereas social capital exerts a stronger direct influence. The findings extend the Resource-Based View and Dynamic Capabilities Theory and provide practical insights for enhancing cooperative sustainability.